If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2 + -1u)(5u + -8) = 0 Reorder the terms: (2 + -1u)(-8 + 5u) = 0 Multiply (2 + -1u) * (-8 + 5u) (2(-8 + 5u) + -1u * (-8 + 5u)) = 0 ((-8 * 2 + 5u * 2) + -1u * (-8 + 5u)) = 0 ((-16 + 10u) + -1u * (-8 + 5u)) = 0 (-16 + 10u + (-8 * -1u + 5u * -1u)) = 0 (-16 + 10u + (8u + -5u2)) = 0 Combine like terms: 10u + 8u = 18u (-16 + 18u + -5u2) = 0 Solving -16 + 18u + -5u2 = 0 Solving for variable 'u'. Factor a trinomial. (-2 + u)(8 + -5u) = 0Subproblem 1
Set the factor '(-2 + u)' equal to zero and attempt to solve: Simplifying -2 + u = 0 Solving -2 + u = 0 Move all terms containing u to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + u = 0 + 2 Combine like terms: -2 + 2 = 0 0 + u = 0 + 2 u = 0 + 2 Combine like terms: 0 + 2 = 2 u = 2 Simplifying u = 2Subproblem 2
Set the factor '(8 + -5u)' equal to zero and attempt to solve: Simplifying 8 + -5u = 0 Solving 8 + -5u = 0 Move all terms containing u to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -5u = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -5u = 0 + -8 -5u = 0 + -8 Combine like terms: 0 + -8 = -8 -5u = -8 Divide each side by '-5'. u = 1.6 Simplifying u = 1.6Solution
u = {2, 1.6}
| 9-N=-24 | | Y-4=0.5(x-1) | | 98=2(2w+4)+2w | | 78=2(2w+12)+2w | | 196=102-x | | x+5=4+y | | X-3x+1=0 | | 5x=14x-7 | | 8lnx=-1 | | 2t+1/t-3=1 | | h=3+55t+16t^2 | | 1/3p=5/8 | | 14-2/3=12 | | f(x)=9x/15 | | 3a-42=-3a+12 | | 6b^2+18b+11= | | 5r+10-5r=10 | | 6f-14f+26-3f-15f= | | 3(2x+5)-2(3x-3)=2x-3 | | log0.1/log8 | | m=2x-1 | | −1/4*5/9 | | z^3+4z^2-12z=0 | | 8-.42k=38+k | | 12+4c=6c-32 | | 4m-9=0 | | 12+4c=6c | | 48w^3+32w^2-3w-2=0 | | 555555555555555555555554444444444444444444444444555555555555555555555554444444444444444444444444555555555555555555555554444444444444444444444444555555555555555555555554444444444444444444444444555555555555555555555554444444444444444444444444555555555555555 | | 4a^3-16a^2-9a+36=0 | | V^3-2v^2-63v=o | | 4x^2-5=12 |